Enhanced tomato plant growth in soil under reduced P supply through microbial inoculants and microbiome shifts. Issue 9 (6th August 2019) - Eltlbany, Namis; Baklawa, Mohamed; Ding, Guo-Chun; Nassal, Dinah; Weber, Nino; Kandeler, Ellen; Neumann, Günter; Ludewig, Uwe; van Overbeek, Leo; Smalla, Kornelia
ABSTRACT: Soil microbial communities interact with roots, affecting plant growth and nutrient acquisition. In the present study, we aimed to decipher the effects of the inoculants Trichoderma harzianum T-22, Pseudomonas sp. DSMZ 13134, Bacillus amyloliquefaciens FZB42 or Pseudomonas sp. RU47 on the rhizosphere microbial community and their beneficial effects on tomato plants grown in moderately low phosphorous soil under greenhouse conditions. We analyzed the plant mass, inoculant colony forming units and rhizosphere communities on 15, 22, 29 and 43 days after sowing. Selective plating showed that the bacterial inoculants had a good rhizocompetence and accelerated shoot and root growth and nutrient accumulation. 16S rRNA gene fingerprints indicated changes in the rhizosphere bacterial community composition. Amplicon sequencing revealed that rhizosphere bacterial communities from plants treated with bacterial inoculants were more similar to each other and distinct from those of the control and the Trichoderma inoculated plants at harvest time, and numerous dynamic taxa were identified. In conclusion, likely both, inoculants and the rhizosphere microbiome shifts, stimulated early plant growth mainly by improved spatial acquisition of available nutrients via root growth promotion. At harvest, all tomato plants were P-deficient, suggesting a limited contribution of inoculants and the microbiome shifts to the solubilization of sparingly soluble soil P. Abstract : Tomato plants inoculated with the bacterial strains showed a remarkably enhanced biomass production and nutrient accumulation triggered by the inoculants and likely also by the microbiome shifts.